2023
DOI: 10.1111/febs.16964
|View full text |Cite
|
Sign up to set email alerts
|

The cryo‐EM structure of the BoNT/Wo‐NTNH complex reveals two immunoglobulin‐like domains

Sara Košenina,
Jana Škerlová,
Sicai Zhang
et al.

Abstract: The botulinum neurotoxin‐like toxin from Weissella oryzae (BoNT/Wo) is one of the BoNT‐like toxins recently identified outside of the Clostridium genus. We show that, like the canonical BoNTs, BoNT/Wo forms a complex with its non‐toxic non‐hemagglutinin (NTNH) partner, which in traditional BoNT serotypes protects the toxin from proteases and the acidic environment of the hosts' guts. We here report the cryo‐EM structure of the 300 kDa BoNT/Wo‐NTNH/Wo complex together with pH stability studies of the complex. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…In this issue of The FEBS Journal, Kosenina et al [13] reported the cryo-EM structure of the M-PTC of BoNT/Wo. The structure reveals that BoNT/Wo and NTNH/Wo form an interlocked compact complex and the overall architecture is highly similar to the crystal structures of the M-PTCs of BoNT/A and BoNT/E that are encoded in the ha and orfX NGC, respectively (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of The FEBS Journal, Kosenina et al [13] reported the cryo-EM structure of the M-PTC of BoNT/Wo. The structure reveals that BoNT/Wo and NTNH/Wo form an interlocked compact complex and the overall architecture is highly similar to the crystal structures of the M-PTCs of BoNT/A and BoNT/E that are encoded in the ha and orfX NGC, respectively (Fig.…”
Section: Introductionmentioning
confidence: 99%